PENGARUH FAKTOR ORGANISASIONAL PADA STRES KERJA PARA PERAWAT DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL PEMODERASI - Rumaningsih(UTP Surakarta), Mrihrahayu (Manajemen Bisnis Syariah, 2011)
One of work resistors of employee performance is stress. Stress can influencesomebody in any different way and various effect depend on the individual condition andthe potential source of evaluated job pressure, it may rise stress to somebody but not for theothers.The intention of this research is (1) to test the Influence of organizationalvariables (role conflict, blocked career, alienation, work over load, and unfavourablework environment) of work stress. (2) to test the Influence of variable of job experience asmoderation variable of work stress.The typical data used in this research is primary data which is taken away fromall nurses of Public Hospital of Moewardi Surakarta. 88 nurses are as the samplesdetermined by using stratified random sampling.The result of developed from multiple regression analysis shows that there ispositive influence of organizational variable to work stress of nurses. It indicates thatevery organizational variable improvement ; i.e role conflict, blocked career, alienation,work over load, and unfavourable work environment will improve work stressThis case performs that the individual difference from work experience point ofview taken an important role in facing the work reality. Individual who remains to belonger stay in work is the one who can hold up the stress, and then she/he developesmechanism to overcome it. Because mechanism development takes much time, so thelonger experience possessed by the nurse, the more possibility she can adapt to work stressBased on the result of data analysis that can be given some suggestion as follows.Considering organizational variable has a positive influence to nurse´s work stress, hencethe hospital management can execute some steps which could probably lessen the stress.The ways that can be done are; on the case of role conflict, the hospital management shallimprove the knowledge of nurse authority and its boundary also makes the target and jobplanning clear by using communications channel effectively. On blocked careerresistance, the information of carrier level is very needed ; On the separation case is notneeded to be controlled extremely; on responsibility work case may review each work´sunit adapting to its specified occupation; on environmental work case is needed to bearranged well, especially at work room which usually depend on visitors. Continuousstudy is needed by hospital management to anticipate nurse´s behavior changes atcomplicated environment work.Keyword: organizational factor and work stress